Determining the Most Stable Structure of Benzamided Derivatives Using Density Functional Theory (DFT) - Cinthia Uly Hotnami Sinaga; Asep Wahyu Nugraha (Universitas Negeri Medan, 2021)
This study aims to determine the energy change ∆E and determine the most stable compound based on computation results using the Density Functional Theory (DFT) method. In determining the energy change ∆E and determining the most stable compound, computational chemical calculations were used using NWChem version 6.6 software with the DFT method with the B3LYP / 3-21G base set hybrid function, the results of the calculations were visualized using the Jmol software. The results of computational calculations on the compound Benzamide is 57467.3632844735 kJ / mol, (4 - chlorocarbonyl - benzial) - pyridine acid carbamics - 3 - ilmetyl ester is 641022.0125237265 kJ / mol, (4- phenylcarbamil benzyl) - pyridine acid carbamic - 3 - ilmetyl ester of 491144.0953277345 kJ / mol, [4- (2-nitro - phenyl carbamoyl) - benzyl] - pyridine acid carboxy - 3 - ilmetyl ester of 1031145,366027853 kJ / mol while for [4 - 2 (amino - phenyl carbamyl) - benzyl) - carboxylic acid - 3 - ilmetyl ester of -1034711.17423932 kJ / mol. Based on these data it can be concluded that [4 - 2 (amino - phenyl carbamyl) - benzyl) - carboxylic acid - 3 - ilmetyl ester is the most stable compound formed because of its lowest price (exothermic)